Development of Interactive Multimedia Applications for Local Culture Awareness - Ziad Iqbal, Muhammad; Firmansyah; Pratama, Yusuf Hendra; Wijaya, Setiawan Ardi (Indonesian Journal of Modern Science and Technology, 2025)
Local culture is a valuable heritage that needs to be introduced and preserved, especially in the face of globalization, which causes younger generations to become increasingly disconnected from their cultural identity. This study aims to develop an interactive multimedia application based on Android as a tool for educating and introducing local culture to high school students. The Research and Development (R&D) method with the ADDIE approach (Analysis, Design, Development, Implementation, and Evaluation) was employed. The test subjects were 60 eleventh-grade students from a high school in West Java. The developed application, named BudiLokal, contains various cultural content, including traditional music, dance, folk tales, musical instruments, and interactive audio-visual quizzes. Evaluation was conducted using a usability questionnaire based on the System Usability Scale (SUS) and pre- and post-tests to measure improvements in student understanding. The research results indicated an average SUS score of 82 (excellent category) and a post-test score increase of 21.8 points compared to the pre-test (p < 0.001). Additionally, 88% of the respondents stated that the application made them more interested in learning about local culture. These findings support the multimedia learning theory, which suggests that presenting material through a combination of text, images, sound, and animation can significantly improve understanding and motivation to learn. This study recommends further development of the application by incorporating Augmented Reality (AR) and Virtual Reality (VR) features for a more immersive learning experience. The BudiLokal application has proven to be an innovative solution in cultural preservation through an adaptive educational approach aligned with technological advancements.